A psychometric analysis of the Ottawa self-injury inventory-f. Issue 1 (2nd January 2018) - Brown, Joshua Travis; Volk, Fred; Gearhart, Gabrielle L.
ABSTRACT: Objective : This study seeks to evaluate the psychometric properties of the Ottawa Self-Injury Inventory-Functions (OSI-F) for assessing nonsuicidal self-injury (NSSI), a condition for further study in the DSM-5.Participants : Participants included 345 students who indicated a history of self-injury in a university counseling center over six semesters from August 2009 to May 2012.Method : Participants completed the OSI-F as a measure on the psychological intake for the university counseling center.Results : Factor analysis, Cronbach's alpha coefficients, independent sample t tests, and correlations were examined and demonstrated adequate reliability and validity.Conclusions : A three-factor solution emerged from the restructured OSI-F relating to Affect Regulation, Exhilaration, and Release . Affect regulation dimensions were predictive of continuing to self-injure and related to depression, anxiety, and overall mental health. Additionally, women were more likely to attribute self-injuring to affect regulation.